2011
DOI: 10.1111/j.1755-3768.2010.02093.x
|View full text |Cite
|
Sign up to set email alerts
|

Corneal biomechanics measured with the ocular response analyser in patients with unilateral open-angle glaucoma

Abstract: . Purpose:  To evaluate the relationship between biomechanical properties of the cornea and intraocular pressure (IOP) and the role of biomechanical properties in eyes of patients with unilateral primary open‐angle glaucoma (POAG). Methods:  The biomechanical properties of corneal hysteresis (CH) and the corneal resistance factor (CRF) were measured with the ocular response analyser (ORA). In an experimental setting, three human donor eyes with Schiotz‐tonometry‐controlled IOP were investigated. In addition, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Only these adjusted parameters can be used for the interpretation of biomechanical differences [20][21][22][23][24][25][26][27]. Most of the published studies on ORA measurements do not consider these dependencies in their analysis.…”
Section: Discussionmentioning
confidence: 97%
“…Only these adjusted parameters can be used for the interpretation of biomechanical differences [20][21][22][23][24][25][26][27]. Most of the published studies on ORA measurements do not consider these dependencies in their analysis.…”
Section: Discussionmentioning
confidence: 97%
“…3539 The reported CH and CRF values varied among these studies. Previous studies have reported that CH was 7.7 to 10.0 and CRF was 7.8 to 11.2 in POAG 3638 or NTG, 3739 whereas CH have been reported as between 9.5 to 11.1 and reported CRF values were between 9.2 to 11.0 in normal control.…”
Section: Discussionmentioning
confidence: 99%
“…Kotecha et al described an IOP-independent corneal factor (corneal constant factor; mm Hg) and demonstrated that this parameter increased with thicker CCT and decreased with age [12]. Other studies have also found an association between greater CH, greater CCT, and lower IOP [6, 13, 14]. One such study looking at 207 normal eyes demonstrated only a moderate correlation between CH and increasing CCT suggesting CH measurements may reflect different aspects of biomechanical rigidity [6].…”
Section: Discussionmentioning
confidence: 99%
“…One such study looking at 207 normal eyes demonstrated only a moderate correlation between CH and increasing CCT suggesting CH measurements may reflect different aspects of biomechanical rigidity [6]. In contrast, a study on patients with unilateral POAG found that CH but not CRF was significantly correlated with IOP concluding that once CH is corrected for IOP, there is no difference in corneal biomechanical properties between eyes with and without POAG [13]. Due to these findings it is important to take both CH and CRF into consideration.…”
Section: Discussionmentioning
confidence: 99%